If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + 9 = c + -3 Reorder the terms: 9 + 5c = c + -3 Reorder the terms: 9 + 5c = -3 + c Solving 9 + 5c = -3 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 9 + 5c + -1c = -3 + c + -1c Combine like terms: 5c + -1c = 4c 9 + 4c = -3 + c + -1c Combine like terms: c + -1c = 0 9 + 4c = -3 + 0 9 + 4c = -3 Add '-9' to each side of the equation. 9 + -9 + 4c = -3 + -9 Combine like terms: 9 + -9 = 0 0 + 4c = -3 + -9 4c = -3 + -9 Combine like terms: -3 + -9 = -12 4c = -12 Divide each side by '4'. c = -3 Simplifying c = -3
| X-64=-6x+62 | | 6x+4x-2=16 | | 44=-4(1+6b)-6(-5b-1) | | 59+11p=-29 | | 3(5e-3)=e+4 | | 6a+a=84 | | 30(6)+5y=90 | | X-43=-4x+27 | | 8x+10y=12-8x | | .45x=9 | | 140+2x-y=180 | | 3(5x-5)=x+10 | | 0=4.9t^2-14.7t | | 20x-x^2=100 | | 3+5h=7+2h | | 8(4r-9)=r+27 | | x+(x+4)+(x+8)=21 | | -7-(n-1)=-6(1-2n) | | y=x^2+7x+9 | | 4x-11=x-9 | | 3a+3=54 | | 8(-1+5x)=112 | | 30=9x+y | | x+10-7=4(x+6)-2(3x+3) | | 103-x=2x+6x-7 | | 8w-13w=25 | | 7b^2+-14b+1=0 | | 4x+11=5x-5 | | 4x+8=2x+31+51 | | 12+40=62 | | 3k-1=7x+2 | | 6+2(x+7)=10-3(x-3) |